PRONOMINA BAHASA NGALUM - Yohanis Sanjoko (Balai Bahasa Provinsi Papua, 2019)
Ngalum language is a local language in Papua Province that has many spoken language. Its native speaker is Ngalum people in Oksibil valley, Okisop, and Okbon, Kabupaten Pegunungan Bintang. As like as the other language in the world, Ngalum language has some word classes. One of them is pronoun. This paper uses descriptive method by three steps, that is to collect data, to analyze data, and to describe data. Its collecting data uses the conversation method by provocative technique as basic technique and face to face technique, and note technique as the next technique. Analyzing of data uses distributional method. There are three pronouns in Ngalum language. There pronouns consist of (1) personal pronoun, (2) demonstrative pronoun, and (3) interrogative pronoun.